The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1111/j.1365-2885.2004.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and allometric scaling of s(+)‐ketoprofen pharmacokinetics and pharmacodynamics: a retrospective analysis

Abstract: Interspecies scaling of pharmacokinetic (PK) parameters is commonplace in drug development. However, information about proportionality of pharmacodynamic (PD) parameters in different species is scarce. We investigated the feasibility of allometric scaling of PK and PD parameters of s(+)-ketoprofen (sKTP) using the literature data from several animal species. Two different indirect response models were proposed to characterize sKTP inhibitory effects on synthesis of thromboxane B(2) (TXB(2)) and prostaglandin E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…Little is known about allometric relationships in PD. Few studies have reported allometric scaling of PD-related parameters via modeling approaches (Gronert et al, 1995;Lepist and Jusko, 2004). As expected, the pharmacologic parameters of rHuEPO (S max and SC 50 ) did not follow allometric principles but may be more related to other factors such as receptor density and/or structural homology of EPO or erythropoietin receptor between species.…”
Section: Pkmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about allometric relationships in PD. Few studies have reported allometric scaling of PD-related parameters via modeling approaches (Gronert et al, 1995;Lepist and Jusko, 2004). As expected, the pharmacologic parameters of rHuEPO (S max and SC 50 ) did not follow allometric principles but may be more related to other factors such as receptor density and/or structural homology of EPO or erythropoietin receptor between species.…”
Section: Pkmentioning
confidence: 99%
“…These offer the opportunity to assess both pharmacologic (capacity, sensitivity) factors and systemic variables (biochemical, physiological). The former are likely to exhibit genetic differences, whereas the latter are more apt to obey allometric principles (Lepist and Jusko, 2004).…”
mentioning
confidence: 99%
“…In particular, drug metabolism is an area where methods based on allometric scaling principles have become a basis for the scaling preclinical of pharmacokinetic (PK) models to predict the time course of drug concentrations in man (4,5). It has been hypothesized (6)(7)(8) that similar methods may also be used to scale integrated pharmacokinetic-pharmacodynamic (PK-PD) models between species to predict time course of drug effects in man. However, currently there is very limited evidence that this is indeed the case.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that PGE 2 can be used as a specific biomarker to explain and understand the variability in the therapeutic of these drugs [12] . Recently, efforts have been made to establish the relationship between biomarkers, pain measurement and safety [13][14][15][16] . However, information on the integrated pharmacokinetic-pharmacodynamic profiles of these drugs under normal and chronic inflammatory conditions is still limited.…”
Section: Introductionmentioning
confidence: 99%